Mental Health of Z-Generation Analysis of Learning Process and Social Interaction - Ali, Muhammad; Retno, Wahyu (Tarbawi : Jurnal Ilmu Pendidikan, 2024)
Mental health is a condition where a person usually behaves and has no complaints either physically or mentally, and also the ability of humans to adapt to nature and other humans. However, the phenomenon in the reality of life is that there is much data on emotional disorders, behavioral disorders, depression, anxiety, and ending life by suicide among adolescents. Several factors cause mental health conditions in adolescents to experience disorders, including being influenced by the learning process and social interaction. This study partially and simultaneously analyzes adolescents' mental health regarding the learning process and social interaction. To achieve this goal, the approach used in this study is quantitative correlational for data collection using a questionnaire distributed to 109 adolescents who are still in MTs Ma'arif Balong. This study proves that the learning process and social interaction simultaneously affect adolescent mental health significantly, with an influence of 78.3%. While partially mental health is influenced by 47.2% of the learning process factor, and 59.3% is influenced by social interaction. Thus, parents and educators need to be models in a healthy mental life and create a conducive environment for the development of adolescent mental health.